History, Structure and Agency in Global Health Governance; Comment on "Global Health Governance Challenges 2016 - Are We Ready?" - Stephen Gill; Solomon R. Benatar (Kerman University of Medical Sciences, 2017)
Ilona Kickbusch's thought provoking editorial is criticized in this commentary, partly because she fails to refer to previous critical work on the global conditions and policies that sustain inequality, poverty, poor health and damage to the biosphere and, as a result, she misreads global power and elides consideration of the fundamental historical structures of political and material power that shape agency in global health governance. We also doubt that global health can be improved through structures and processes of multilateralism that are premised on the continued reproduction of the ecologically myopic and socially unsustainable market civilization model of capitalist development that currently prevails in the world economy. This model drives net financial flows from poor to rich countries and from the poor to the affluent and super wealthy individuals. By contrast, we suggest that significant progress in global health requires a profound and socially just restructuring of global power, greater global solidarity and the "development of sustainability."